2006
DOI: 10.2105/ajph.2005.063263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Childhood Sexual Abuse and Physical Trauma in an HIV-Positive Sample From the Deep South

Abstract: We examined prevalence and predictors of trauma among HIV-infected persons in the Deep South using data from the Coping with HIV/AIDS in the Southeast (CHASE) study. Over 50% of CHASE participants were abused during their lives, with approximately 30% experiencing abuse before age 13, regardless of gender. Caregiver characteristics were associated with childhood abuse. Abuse is related to increases in high-HIV-risk activities. The findings help explain why people engage in such high-risk activities and can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 35 publications
3
76
0
Order By: Relevance
“…While there is little empirical evidence of the relation between sexual abuse and HIV infection among Aboriginal people, there is a large body of literature that strongly links previous sexual trauma with HIV vulnerability among vulnerable populations (Braitstein et al, 2003;Whetton et al, 2006). The focus is often on women because sexual abuse is twice as likely to target females as males according to one study (Libby et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While there is little empirical evidence of the relation between sexual abuse and HIV infection among Aboriginal people, there is a large body of literature that strongly links previous sexual trauma with HIV vulnerability among vulnerable populations (Braitstein et al, 2003;Whetton et al, 2006). The focus is often on women because sexual abuse is twice as likely to target females as males according to one study (Libby et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite scarcity of empirical evidence of the relation between sexual abuse, for instance, and HIV infection among Aboriginal people, a large body of literature strongly links HIV susceptibility among vulnerable populations to previous sexual trauma (Braitstein et al, 2003;Whetton et al, 2006). Of note here is that, it is widely accepted that sexual abuse in…”
Section: Policies Of Forced Assimilation Are Prime Causes Of Poor Heamentioning
confidence: 99%
“…Research (Jones, et al, 2010b;Whetten, 2006;Paolucci & Violato, 2001;McCauley et al, 1997). However, the results of the study found no difference in the relationship between level of exposure to CSA and multiple partners, knowledge of HIV, and sexual self-efficacy-the remaining behaviors organized under the sexual risk behaviors variable.…”
Section: Discussion Of Findings: Research Questionsmentioning
confidence: 84%
“…Studies have long established that victims of CSA exhibit greater sexual risk behaviors than persons who have not experienced CSA (Parcesepe et al, 2015;O'Cleirigh, Safren, & Mayer, 2012;Sikkema et al 2013;Pence et al, 2012;Jones, et al, 2010b;Whetten, 2006;McCauley et al, 1997). The few studies conducted in developing countries on the matter have also produced the same results, indicating the pervasiveness of higher levels of sexual risk behaviors among victims of CSA, regardless of country of origin (Parcesepe et al, 2015;Richter et al, 2014;Longman-Mills et al, 2013;Tomaszewski, 2012).…”
Section: Childhood Sexual Abusementioning
confidence: 96%
See 1 more Smart Citation